2014
DOI: 10.1118/1.4868459
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam tracking using ultrasound motion detection

Abstract: Purpose: The use of motion mitigation techniques such as tracking and gating in particle therapy requires real-time knowledge of tumor position with millimeter precision. The aim of this phantom-based study was to evaluate the option of diagnostic ultrasound (US) imaging (sonography) as real-time motion detection method for scanned heavy ion beam irradiation of moving targets. Methods: For this pilot experiment, a tumor surrogate was moved inside a water bath along two-dimensional trajectories. A rubber ball w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…A phantom-based experiment has shown that real-time ultrasound motion detection and beam tracking enable considerably reducing the interplay effects in scanned ion beam radiotherapy. 62 Apart from the ultrasound beam former and conventional diagnostic probe, the tested device consisted of a special tracking probe with two 5.5-MHz, 64-element phased-array ultrasound transducers encompassing two perpendicular image planes. 62 The tracking frame rate of 6.7 Hz (150 ms per frame) of the ultrasound probe was influenced by several factors such as the finite speed of sound and the time required for image processing.…”
Section: External Surrogatementioning
confidence: 99%
“…A phantom-based experiment has shown that real-time ultrasound motion detection and beam tracking enable considerably reducing the interplay effects in scanned ion beam radiotherapy. 62 Apart from the ultrasound beam former and conventional diagnostic probe, the tested device consisted of a special tracking probe with two 5.5-MHz, 64-element phased-array ultrasound transducers encompassing two perpendicular image planes. 62 The tracking frame rate of 6.7 Hz (150 ms per frame) of the ultrasound probe was influenced by several factors such as the finite speed of sound and the time required for image processing.…”
Section: External Surrogatementioning
confidence: 99%
“…Relative to X‐ray based techniques, the use of US for intra‐fraction motion management is at an early stage. In particle therapy the feasibility of ultrasound based beam tracking has been reported by Prall et al . They showed that delay compensation is possible via neural networks and present experimental data indicating the feasibility of ultrasound based compensation without tracking parameters from treatment planning.…”
Section: Motion Monitoring Image Guided Particle Therapymentioning
confidence: 64%
“…Information on the lag time of a motion detection system would be required if motion-adaptive actions are taken based on this system. So far, ultrasound imaging has been shown to be feasible to guide motion compensation with ion beam tracking 41 and multileaf collimator tracking. 22 Both studies used simple rigid spheres moved in water tanks as targets.…”
Section: Discussionmentioning
confidence: 99%